Transplacental immune modulation with a bacterial-derived agent protects against allergic airway inflammation - Mincham, K.; Scott, N.; Lauzon-Joset, J.; Leffler, J.; Larcombe, Alexander; Stumbles, P.; Robertson, S.; Pasquali, C.; Holt, P.; Strickland, D. (2018)
Chronic allergic inflammatory diseases are a major cause of morbidity, with allergic asthma alone affecting over 300 million people worldwide. Epidemiological studies demonstrate that environmental stimuli are associated with either the promotion or prevention of disease. Major reductions in asthma prevalence are documented in European and US farming communities. Protection is associated with exposure of mothers during pregnancy to microbial breakdown products present in farm dusts and unprocessed foods and enhancement of innate immune competence in the children. We sought to develop a scientific rationale for progressing these findings toward clinical application for primary disease prevention. Treatment of pregnant mice with a defined, clinically approved immune modulator was shown to markedly reduce susceptibility of their offspring to development of the hallmark clinical features of allergic airway inflammatory disease. Mechanistically, offspring displayed enhanced dendritic cell-dependent airway mucosal immune surveillance function, which resulted in more efficient generation of mucosal-homing regulatory T cells in response to local inflammatory challenge. We provide evidence that the principal target for maternal treatment effects was the fetal dendritic cell progenitor compartment, equipping the offspring for accelerated functional maturation of the airway mucosal dendritic cell network following birth. These data provide proof of concept supporting the rationale for developing transplacental immune reprogramming approaches for primary disease prevention.